Testosterone levels of children with a diagnosis of developmental stuttering - Selçuk EB; Erbay LG; Özcan ÖÖ; Kartalcı S; Batcıoğlu K (Dove Medical Press, 2015)
Engin Burak Selçuk,1 Lale Gönenir Erbay,2 Özlem Özel Özcan,3 Sükrü Kartalci,2 Kadir Batcioğlu4 1Department of Family Medicine, 2Department of Psychiatry, 3Department of Child and Adolescent Psychiatry, Inonu University Medical Faculty, 4Inonu University Pharmacy Faculty, Malatya, Turkey Background: Stuttering is defined as a disruption in the rhythm of speech and language articulation, where the subject knows what he/she wants to say, but is unable to utter the intended word or phrase fluently. The effect of sex on development and chronicity of stuttering is well known; it is more common and chronic in males. We aimed to investigate the relationship between developmental stuttering and serum testosterone levels in this study.Materials and methods: In this study, we evaluated a total of 50 children (7–12 years of age); eight (16%) were female and 42 (84%) were male. Twenty-five children who stutter and 25 typically fluent peers with the same demographic properties (ages between 7 years and 12 years) were included in this study. The testosterone levels of the two groups were determined in terms of nanogram per milliliter (ng/mL) by enzyme-linked immunosorbent assay. The difference between the means of the two groups was analyzed.Results: The medians of the testosterone levels of the stutterer and control groups were determined as 20 ng/mL (range =12–184 ng/mL) and 5 ng/mL (range =2–30 ng/mL), respectively. Testosterone levels of the stutterer group were significantly higher than in the control group (I=0.001). Besides, there was a significant correlation between the severity of the stuttering and testosterone levels in the stutterer group (I=0.0001).Conclusion: The findings of this study show that testosterone may have an effect on the severity of developmental stuttering and on the clinical differences between sexes. However, further investigations are needed to show that testosterone may play a role in the etiology of developmental stuttering. Keywords: children, stuttering, testosterone